Karakteristik Unjuk Kerja 2 Pompa Sentrifugal Dengan Susunan Seri Sebagai Turbin Pat - Lubis, Sudirman; Siregar, Irpansyah; Siregar, Ahmad Marabdi (Fakultas Teknik UMSU, 2020)
The pump is a device used to move fluid from one place to another through a media pipe or channel. The energy in the fluid is produced from the impeller which converts the kinetic energy (velocity) of the liquid into potential (dynamic) energy. Besides being used to move fluid (fluid) at this time the pump can also be used as a turbine by changing the working principle of the pump by giving a drop of water at an altitude to rotate the impeller on the pump so that the pump can operate upside down or called a pump as turbine), in this study the impeller on the pump as a turbine is driven by a water flow or water pressure that is large enough, the water flow is sourced from two centrifugal pumps with a series arrangement that functions as a driving force or fluid distributor which is assumed to be a high water fall or head. The use of centrifugal pumps with a series arrangement is so as to produce a large head to get a high water fall or a maximum head for turning a pump as a turbine. This study uses an experimental method that is using two centrifugal pumps as a fluid distributor and one pump that is used as a turbine and uses a variation of 5 watt and 10 watt light bulb. From the calculation of the suction pump and pump as a turbine without using a light bulb pump speed namely 920.5 rpm and the specific speed of the turbine produced is 76.61 rpm. by using a 5 watt light bulb load the pump rotation speed is 553 rpm and the specific turbine speed produced is 44.24 rpm, using a 10 watt light bulb load the pump rotation speed is 335 rpm and the specific turbine speed produced is 26.8 rpm. The greater the value of the pump head, the resulting water discharge will be smaller and vice versa, the size and size of the pump head obtained is also influenced by the presence of load on theturbine.